Learning design Rashomon I – supporting the design of one lesson through different approaches - Donatella Persico; Francesca Pozzi; Stamatina Anastopoulou; Gráinne Conole; Brock Craft; Yannis Dimitriadis; Davinia Hernández-Leo; Yael Kali; Yishay Mor; Mar Pérez-Sanagustín; Helen Walmsley (Association for Learning Technology, 2013)
This paper presents and compares a variety of approaches that have been developed to guide the decision-making process in learning design. Together with the companion Learning Design Rashomon II (Prieto et al., 2013), devoted to existing tools to support the same process, it aims to provide a view on relevant research results in this field. The common thread followed in these two contributions is inspired by Kurosawa's Rashomon film, which takes multiple perspectives on the same action. Similarly, in this paper, Rashomon I, a lesson on “Healthy Eating” is analysed according to five different approaches, while the Rashomon II paper is used to exemplify the affordances of different tools. For this reason, this paper does not follow the conventional structure of research papers (research question, method, results and discussion), but rather it moves from an introduction providing the rationale for the paper, to a description of the five different approaches to learning design (the 4SPPIces Model, the 4Ts, the e-Design Template, the Design Principles Database and the Design Narrative) and then to a discussion of their similarities and differences to inform the choice of potential users.